Starlit Waters : British Sculpture : An International Art : 1968-1988. - Tate Gallery, Liverpool (Liverpool : Tate Gallery, 1988)
Art & Language ; Cragg, Tony ; Craig-Martin, Michael ; Deacon, Richard ; Flanagan, Barry ; Fulton, Hamish ; Gormley, Antony ; Finlay, Ian Hamilton ; Hilliard, John ; Houshiary, Shirazeh ; Kapoor, Anish ; Latham, John ; Long, Richard ; etc.
Starlit Waters : British Sculpture : An International Art : 1968-1988, Tate Gallery, Liverpool, 28 May - 4 September 1988
boek